Participatory Politics and Citizen Journalism in a Networked Africa
XVI, 291 p.
Keywords: This book investigates the role of citizen journalism in railroading social and political changes in sub-Saharan Africa. Case studies are drawn from research conducted by leading scholars from the fields of media studies, journalism, anthropology and history, who uniquely probe the real impact of technologies in driving change in Africa.